Comparative genomics of the tardigrades Hypsibius dujardini and Ramazzottius varieornatus - Yoshida, Yuki; Koutsovoulos, Georgios; Laetsch, Dominik R.; Stevens, Lewis; Kumar, Sujai; Horikawa, Daiki D.; Ishino, Kyoko; Komine, Shiori; Kunieda, Takekazu; Tomita, Masaru; Blaxter, Mark; Arakawa, Kazuharu (PLOS Biology, 2017)
Author summary Tardigrades are justly famous for their abilities to withstand environmental extremes. Many freshwater and terrestrial species can undergo anhydrobiosis—life without water—and thereby withstand desiccation, freezing, and other insults. We explored the comparative biology of anhydrobiosis in 2 species of tardigrade that differ in the mechanisms they use to enter anhydrobiosis. Using newly assembled and improved genomes, we find that Ramazzottius varieornatus, a species that can withstand rapid desiccation, differs from Hypsibius dujardini, a species that requires extended preconditioning, in not showing a major transcriptional response to anhydrobiosis induction. We identified a number of genetic systems in the tardigrades that likely play conserved, central roles in anhydrobiosis as well as species-unique components. Compared to previous estimates, our improved genomes show much reduced levels of horizontal gene transfer into tardigrade genomes, but some of the identified horizontal gene transfer (HGT) genes appear to be involved in anhydrobiosis. Using the improved genomes, we explored the evolutionary relationships of tardigrades and other molting animals, particularly nematodes and arthropods. We identified conflicting signals between sequence-based analyses, which found a relationship between tardigrades and nematodes, and analyses based on rare genomic changes, which tended to support the traditional tardigrade-arthropod link.